2013
DOI: 10.5194/acp-13-6965-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the mountain–plains solenoid and cold pool dynamics on the diurnal variation of warm-season precipitation over northern China

Abstract: Convection-permitting numerical experiments using the Weather Research and Forecasting (WRF) model are performed to examine the impact of a thermally driven mountain–plains solenoid (MPS) on the diurnal variation of warm-season precipitation over northern China. The focus of the analyses is a 15-day simulation that uses the 8-day average of the NCEP GFS gridded analyses at 00:00 UT between 17 and 24 June 2004 for the initial conditions and the 8-day averages at 00:00, 06:00, 12:00, and 18:00 UT for the lateral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…3 and 4, respectively. Consistent with previous studies (Carbone et al, 2002(Carbone et al, , 2008Wang et al, 2004;BZS11;Xu and Zipser, 2011), the diurnal variation of precipitation has an evident phase-delayed feature east of the big topography (TP and the Rocky Mountains, Fig. 2).…”
Section: Wave-number-frequency Spectral Analysis and Decompositionsupporting
confidence: 91%
See 1 more Smart Citation
“…3 and 4, respectively. Consistent with previous studies (Carbone et al, 2002(Carbone et al, , 2008Wang et al, 2004;BZS11;Xu and Zipser, 2011), the diurnal variation of precipitation has an evident phase-delayed feature east of the big topography (TP and the Rocky Mountains, Fig. 2).…”
Section: Wave-number-frequency Spectral Analysis and Decompositionsupporting
confidence: 91%
“…Recent studies have explored diurnal variation of precipitation using the National Oceanic and Atmospheric Administration (NOAA) Climate Prediction Center(CPC) morphing technique (CMORPH) rainfall data set and have shown that precipitation propagates downslope, eastward/southeastward, at a speed of ∼ 13 ms −1 from the eastern edge of the TP, the second-step terrain in northern China (He and Zhang, 2010;BZS11;Sun and Zhang, 2012). Through convectionpermitting simulations that successfully captured the diurnal precipitation propagation, Bao and Zhang (2013) further investigated what controls the diurnal peak propagation speed. Consistent with Trier et al (2010), they found that besides the impact of the mountains-plains solenoids (MPSs), the steering-level mean flow and the cold pool dynamics both play an essential role in the propagation and maintenance of the precipitation peak over the plains.…”
Section: Introductionmentioning
confidence: 99%
“…Another sensitivity experiment NOVAP was performed similarly to the IDEAL experiment except that the evaporation of liquid water, which prevents the cold pool generation from moisture convection process, was turned off. A similar methodology has been used to study diurnal cycles of precipitation in many different regions (Trier et al, 2010;Sun and Zhang, 2012;Bao and Zhang, 2013;Chen et al, 2016Chen et al, , 2017. The biggest advantage of this method is that it is able to capture the general characteristics of the diurnal cycle of precipitation and the related dynamical processes instead of just focusing on a single case.…”
Section: Observation Dataset and Methodologymentioning
confidence: 99%
“…Interactions between land breeze and prevailing wind are likely to produce precipitation over the coastal area or tropical islands (Keenan et al, 1988;Chen et al, 2017). Recent studies (Bao et al, 2013;Chen et al, 2016Chen et al, , 2017 have also found that convectively driven cold pools and latent cooling, as well as environmental wind and moisture, may play important roles in the propagation and maintenance of diurnal rainfall in coastal regions. How cold pools and latent cooling affect the diurnal cycle of rainfall and related LSB over a tropical island has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling by evaporation of precipitation below convective clouds results in cold pools, which are characterized by a near-surface horizontal flow of relatively cold and dry air. A few studies (e.g., Grabowski et al 2006;Khairoutdinov and Randall 2006;Böing et al 2012;Bao and Zhang 2013;Schlemmer and Hohenegger 2014) investigated how precipitation-driven cold pools aid the transition from shallow to deep convection. Vertical lifting and moisture accumulation at the leading edge of the cold pool play an important role.…”
Section: October 2016 P a N O S E T T I E T A Lmentioning
confidence: 99%